P-D6 Effects of influenza vaccination on lymphoid architecture in HIV+ patients on combination antiretroviral therapy (cART). (January 2016) - Moysi, Eirini; Gonzalez, Louis; Casazza, Joseph; Varghese, George; Pahwa, Rajendra; Pallikkuth, Suresh; Huddleston, David; Koup, Richard; Petrovas, Constantinos; Pahwa, Savita
Abstract : Introduction: Persons with HIV/AIDS have significant morbidity/mortality due to influenza virus and are thus targeted for prevention through immunization. However, despite numerous reports on post-immunization antibody titers, the effects of vaccination on the lymphoid tissue architecture of patients on cART and local virus reactivation have not yet been explored. Methods/Results: Lymph node (LN) -derived cells and tissues from healthy controls and virologically suppressed HIV+ subjects were obtained pre- and post- vaccination and analyzed by polychromatic flow cytometry, multicolour confocal imaging and histocytometry. The effect of influenza vaccination on viral dynamics was determined in sorted LN-CD4 T cell populations by quantifying the de-novo synthesis of early HIV transcripts. Influenza -specific antibody titers were measured by hemagglutination inhibition assay. Tissue structure and follicular organization was notably different between healthy and HIV+ individuals. Flu vaccination differentially affects the lymphoid architecture as well as the frequency of follicular CD4 T cells in these 2 groups, which may explain previous observations of variable B cell responses to immunization in HIV- infected individuals. Furthermore, vaccination exerted an impact on the actively transcribed virus in follicular CD4 T cell populations. Conclusions: Chronic HIV-infection establishes a fingerprint of lymphoid changes that is irreversible by cART. Our study shows that these changes further perturb the antigenic response towards an important immunogen and set the stage for further mechanistic studies that could elucidate ways to enhance immunogenicity in such high-risk populations.